DEFB1 gene polymorphisms and tuberculosis in a Northeastern Brazilian population. - Celerino da Silva, Ronaldo; da Cruz, Heidi Lacerda Alves; Brandão, Lucas André Cavalcanti; Guimarães, Rafael Lima; Montenegro, Lilian Maria Lapa; Schindler, Haiana Charifker; Segat, Ludovica; Crovella, Sergio (Braz J Microbiol, 2016)
β-Defensin-1, an antimicrobial peptide encoded by the DEFB1 gene, is known to play an important role in lung mucosal immunity. In our association study we analyzed three DEFB1 functional polymorphisms -52G>A (rs1799946), -44C>G (rs1800972) and -20G>A (rs11362) in 92 tuberculosis patients and 286 healthy controls, both from Northeast Brazil: no association was found between the studied DEFB1 polymorphisms and the disease. However we cannot exclude that this lack of association could be due to the low number of subjects analyzed, as suggested by the low statistical power achieved for the three analyzed SNPs (values between 0.16 and 0.50).